2005
DOI: 10.1128/aem.71.5.2762-2765.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Gene yggE Functions in Restoring Physiological Defects of Escherichia coli Cultivated under Oxidative Stress Conditions

Abstract: DNA microarray analysis showed that yfiD, yggB, and yggE genes were up-regulated when superoxide dismutase (SOD)-deficient Escherichia coli IM303 (I4) was cultivated under the oxidative stress generated by photoexcited TiO 2 , and pYFD, pYGB, and pYGE were constructed by inserting the respective genes into a pUC 19 vector. The content of reactive oxygen species (ROS) in IM303 (I4) cells carrying pYGE was reduced to 31% of ROS content in the control cells with pUC 19. In the culture of wild-type strain, E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…The results confirmed that exposure to nTiO 2 affects algal growth [3] and photosynthetic activity [12] and that abiotic parameters, such as particle size/aggregation and illumination, are key factors affecting nTiO 2 toxicity [15,16]. The underlying toxicity mechanisms of nTiO 2 nanomaterials have been elucidated to some extent, and they include membrane disruption [17], protein oxidation via reactive oxygen species (ROS) formation [9], and possible DNA damage [18]. Furthermore, persistence and bioaccumulation of nTiO 2 in cells is mostly unknown, and this potentially presents a concern for possible introduction into the food web.…”
Section: Introductionsupporting
confidence: 72%
“…The results confirmed that exposure to nTiO 2 affects algal growth [3] and photosynthetic activity [12] and that abiotic parameters, such as particle size/aggregation and illumination, are key factors affecting nTiO 2 toxicity [15,16]. The underlying toxicity mechanisms of nTiO 2 nanomaterials have been elucidated to some extent, and they include membrane disruption [17], protein oxidation via reactive oxygen species (ROS) formation [9], and possible DNA damage [18]. Furthermore, persistence and bioaccumulation of nTiO 2 in cells is mostly unknown, and this potentially presents a concern for possible introduction into the food web.…”
Section: Introductionsupporting
confidence: 72%
“…Moreover, spontaneously derived superoxide dismutase (SOD)-deficient E. coli cells induce yggE (23). Therefore, yggE is proposed to act as an auxiliary defense system against oxidative stress (23). In accordance with this notion, intracellular ROS levels were lower in SOD-deficient E. coli strains that overexpressed yggE than in E. coli strains that did not do so (25).…”
Section: Discussionsupporting
confidence: 67%
“…YggE has been predicted to function as an auxiliary defense system against oxidative stress (23). We therefore hypothesized that YggE is a fitness factor for E. coli Nissle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytoplasmic YajQ protein was the single additional protein modified only during UV-A photocatalysis and not with TiO 2 in the dark, in comparison to the others, which were already modified in the dark (TiO 2 cytotoxic effect). The YggE gene product is involved in the reduction of the intracellular ROS level and is therefore responsible for lowering the concentration of ROS to a tolerated level (47). ArcA is a two-component response regulator involved in the oxidative stress response (48,49), and YajQ is involved in ROS detoxification mechanism (50).…”
Section: Discussionmentioning
confidence: 99%